BUILD STUDENT CHARACTER THROUGH ISLAMIC RELIGIOUS EDUCATION - Imam Tabroni; Alya Siti Nurhasanah; Vina Maulidina (SOKO GURU: Jurnal Ilmu Pendidikan, 2021)
Character education is important for human life, so the role played by the world of education must not only show moral knowledge, but also love and be willing to take moral action. This paper will discuss the formation of student character through Islamic religious education. Islamic Religious Education (PAI) is one of the most important pillars of character education in the world of education. Character education will grow well if it starts from the instillation of a religious spirit in children, therefore PAI material in schools is one of the supports for character education for students. Through PAI learning, students are taught aqidah as their religious basis, taught the Koran and hadith as a guide for their life, taught fiqh as legal signs in worship, teaches Islamic history as an example of life, and teaches morals as a guide for human behavior whether in the good or bad category. bad. Therefore, the main goal of PAI learning is the formation of personality in students which is reflected in their behavior and mindset in everyday life. In addition, the success of PAI learning in schools is also determined by the application of appropriate learning methods.